Measurement of Attitudes Regarding Foreign Language Skills and Its Relation with Success - Tülin Acar (International Journal of Evaluation and Research in Education (IJERE), 2016)
The aim of this research is to determine the attitudes of secondary level students regarding the skills in English as a Foreign Language and to compare the level of relationship between the academic success at English and the attitudes measured. Attitudes and success levels of the students of secondary education regarding their language skills were found to be high. A significant relationship at a linear low level was observed between the academic success of the students and their attitudes towards English language skills. In this study, the attitudes of high school students measured according to their gender concerning their reading, writing, speaking and listening skills, showed difference in favor of female students. Again, high school students’ attitudes towards writing, speaking and listening skills except for the attitudes towards reading skills do differentiate according to the type of school in which they receive education.